Comparing Politics of Quality in Education - Jaakko Kauko; Tuomas Takala; Risto Rinne (Routledge, 2025)
We start the book with a reiteration of the idea that quality has become one of the most important framing factors in education policies and practices. The introductory chapter coins the concept of quality assurance and evaluation (QAE), its differing and contested interpretations, and its seemingly uniform transnational agenda. The chapter discusses how QAE is linked to the questions of politics and power as well as how it is used as a governance tool. The chapter also describes the project’s ontological premises, which are contingency and complexity theory. These ontological premises are then discussed in the light of contemporary comparative education and political science theories. The book’s analytical framework, called Comparative Analytics of Dynamics in Education Politics (CADEP), is introduced. The CADEP framework focuses the analysis on the dimensions of political situations, political possibilities, and the use of political space. The chapter concludes with a discussion of the book’s aim, which is to analyse how QAE as a transnational flow and governance tool changes the role of state, expertise, governance, and the room for action which exists for politicians, teachers, and other actors in varying contexts.
Politics of Quality in Education: A Comparative Study of Brazil, China and Russia